A clinical prediction score in addition to WHO criteria for anti-retroviral treatment failure in resource-limited settings--experience from Lesotho. - Niklaus Daniel Labhardt (Public Library of Science (PLoS), 2012)
Objective To assess the positive predictive value (PPV) of a clinical score for viral failure among patients fulfilling the WHO-criteria for anti-retroviral treatment (ART) failure in rural Lesotho. Methods Patients fulfilling clinical and/or immunological WHO failure-criteria were enrolled. The score includes the following predictors: Prior ART exposure (1 point), CD4-count below baseline (1), 25% and 50% drop from peak CD4-count (1 and 2), hemoglobin drop≥1 g/dL (1), CD4 count<100/µl after 12 months (1), new onset papular pruritic eruption (1), and adherence<95% (3). A nurse assessed the score the day blood was drawn for viral load (VL). Reported confidence intervals (CI) were calculated using Wilsons method. Results Among 1'131 patients on ART ≥ 6 months, 134 (11.8%) had immunological and/or clinical failure, 104 (78%) had blood drawn (13 died, 10 lost to follow-up, 7 did not show up). From 92 (88%) a result could be obtained (2 samples hemolysed, 10 lost). Out of these 92 patients 47 (51%) had viral failure (≥ 5000 copies), 27 (29%) viral suppression (<40) and 18 (20%) intermediate viremia (40-4999). Overall, 20 (22%) had a score ≥ 5. A score ≥ 5 had a PPV of 100% to detect a VL>40 copies (95%CI: 84-100), and of 90% to detect a VL ≥ 5000 copies (70-97). Within the score, adherence<95%, CD4-count<100/µl and papular pruritic eruption were the strongest single predictors. Among 47 patients failing, 8 (17%) died before or within 4 weeks after being switched. Overall mortality was 4 (20%) among those with score ≥ 5 and 4 (5%) if score<5 (OR 4.3; 95%CI: 0.96-18.84, p = 0.057). Conclusion A score ≥ 5 among patients fulfilling WHO-criteria had a PPV of 100% for a detectable VL and 90% for viral failure. In settings without regular access to VL-testing, this PPV may be considered high enough to switch this patient-group to second-line treatment without confirmatory VL-test.